ALCAM contributes to brain metastasis formation in non-small-cell lung cancer through interaction with the vascular endothelium. Issue 7 (17th February 2020) - Münsterberg, Justine; Loreth, Desirée; Brylka, Laura; Werner, Stefan; Karbanova, Jana; Gandrass, Monja; Schneegans, Svenja; Besler, Katharina; Hamester, Fabienne; Robador, José Ramon; Bauer, Alexander Thomas; Schneider, Stefan Werner; et al.
Abstract: Background: Brain metastasis (BM) in non-small-cell lung cancer (NSCLC) has a very poor prognosis. Recent studies have demonstrated the importance of cell adhesion molecules in tumor metastasis. The aim of our study was to investigate the role of activated leukocyte cell adhesion molecule (ALCAM) in BM formation in NSCLC. Methods: Immunohistochemical analysis was performed on 143 NSCLC primary tumors and BM. A correlation between clinicopathological parameters and survival was developed. Biological properties of ALCAM were assessed in vitro by gene ablation using CRISPR/Cas9 technology in the NCI-H460 NSCLC cell line and in vivo by intracranial and intracardial cell injection of NCI-H460 cells in NMRI- Foxn1 nu/nu mice. Results: ALCAM expression was significantly upregulated in NSCLC brain metastasis ( P = 0.023) with a de novo expression of ALCAM in 31.2% of BM. Moderate/strong ALCAM expression in both primary NSCLC and brain metastasis was associated with shortened survival. Functional analysis of an ALCAM knock-out (KO) cell line showed a significantly decreased cell adhesion capacity to human brain endothelial cells by 38% ( P = 0.045). In vivo studies showed significantly lower tumor cell dissemination in mice injected with ALCAM-KO cells in both mouse models, and both the number and size of BM were significantly diminished in ALCAM depleted tumors. Conclusions: Our findings suggest that elevated levels of ALCAM expression promote BM formation in NSCLC through increased tumor cell dissemination and interaction with the brain endothelial cells. Therefore, ALCAM could be targeted to reduce the occurrence of BM. Key Points: 1. ALCAM expression associates with poor prognosis and brain metastasis in NSCLC. 2. ALCAM mediates interaction of NSCLC tumor cells with brain vascular endothelium. 3. ALCAM might represent a novel preventive target to reduce the occurrence of BM in NSCLC.